2013
DOI: 10.1088/1757-899x/50/1/012071
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of tensile properties of polyester composites reinforced with pineapple leaf fiber and pineapple peduncle fiber

Abstract: A comparison of tensile properties of polyester composites reinforced with pineapple leaf fiber and pineapple peduncle fiber Abstract. Pineapple fiber which is rich in cellulose, relatively inexpensive, and abundantly available has the potential for polymer reinforcement. This research presents a study of the tensile properties of pineapple leaf fiber and pineapple peduncle fiber reinforced polyester composites. Composites were fabricated using leaf fiber and peduncle fiber with varying fiber length and fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Two peaks are observed in the range of 15–18° and 21–23° for most of the natural plant fibers in the earlier studies. [ 56 ] This investigatory result also validates the outcomes of chemical composition analysis, proving the existence of crystalline and amorphous components in the fiber.…”
Section: Resultssupporting
confidence: 69%
“…Two peaks are observed in the range of 15–18° and 21–23° for most of the natural plant fibers in the earlier studies. [ 56 ] This investigatory result also validates the outcomes of chemical composition analysis, proving the existence of crystalline and amorphous components in the fiber.…”
Section: Resultssupporting
confidence: 69%
“…The mechanical properties of PALF-polyester composites at different PALF loading were studied by different researchers [118]. They report that the mechanical properties (tensile strength, tensile modulus, elongation at break, Young's modulus, impact strength, and shear strength) of neat polyester increases with PALF [wt%] and this iomprovement is attributed to the enhancement of fiber-matrix interaction with fiber loading [119,120]. However, the mechanical properties are found to diminish at high fiber loading, due to poor dispersion of fiber in the matrix.…”
Section: Palf Reinforced Polymer Composites 51 Palf-polyester (Ps) mentioning
confidence: 99%
“…Polyester composites reinforced with pineapple leaf and pineapple peduncle fibers results showed that the best‐performing pineapple fiber was the peduncle fiber, which included 4% fiber volume fraction and fiber length of 30 mm. Overall, the tensile qualities of pineapple peduncle fiber were found to be superior to those of pineapple leaf fiber 16 …”
Section: Introductionmentioning
confidence: 90%
“…Overall, the tensile qualities of pineapple peduncle fiber were found to be superior to those of pineapple leaf fiber. 16 In the present investigation, a novel plant fiber from Furcraea selloa K. Koch peduncle has been introduced in the quest of exploring a new cellulosic plant fiber for composite fabrication. Hence an effort has been made for characterization of the fiber through various analytical methods including physical (density, diameter), chemical (cellulose, hemicellulose, lignin, wax, ash, and moisture) mechanical (tensile strength/modulus), thermal (thermal stability) and morphological (surface roughness) analysis.…”
Section: Introductionmentioning
confidence: 99%